Exploring Key Factors and Solutions for English Academic Text Reading Difficulties among Elementary Teacher Education Students - Kaltsum, Honest Ummi; Utami, Ratnasari Diah; Desstya, Anatri; Herliana, Shella; Pitaloka, Sinta Diah Ayu (Universitas Pendidikan Indonesia, 2025)
English academic reading is an essential skill for undergraduates both in English major students and non-English major students. However, many non-English major students, particularly Indonesian Elementary Teacher Education (ETE) students, face significant challenges in comprehending academic English texts. This qualitative study explores the core causes of these difficulties, focusing on linguistic, psychological, environmental, and reading experience factors. Data were collected via interviews with lecturers and students and through focus group discussions (FGDs) to identify potential solutions. Results indicate that linguistic challenges, including academic vocabulary and grammar, and psychological barriers like reading anxiety, are primary obstacles. Although students have access to a conducive learning environment, their reading habits remain limited, averaging only one to three times per week. To address these issues, the study suggests increasing reading frequency and vocabulary mastery[2.1][HH2.2]. Additionally, strategies such as intensive and extensive reading practices, vocabulary development, and skimming and scanning techniques are recommended to improve comprehension. The study concludes by recommending contextually appropriate strategies to enhance academic literacy and foster more effective reading skills among ETE students.